Serum IRAK3 may serve as a prognostic biomarker in acute supratentorial intracerebral hemorrhage: findings from a prospective observational cohort study - Ma, Yijun; Wang, Jun; Tang, Chao; Li, Wei; Lv, Xuan; Zhu, Suijun (Frontiers in Neurology, 2024)
Background Interleukin-1 receptor-associated kinase 3 (IRAK3) modulates neuroinflammation. This study aimed to determine the prognostic role of serum IRAK3 in acute intracerebral hemorrhage (ICH). Methods In this prospective observational cohort study, 152 patients with supratentorial ICH, along with 63 healthy controls, were recruited. Serum IRAK3 levels were measured at the time of enrollment for controls, at admission for all patients, and on poststroke days 1, 3, 5, 7, 10, and 15 in a subset of 63 patients. Stroke severity was assessed using the National Institutes of Health Stroke Scale (NIHSS) and hematoma volume. Poststroke 6-month modified Rankin Scale (mRS) scores were registered, with scores of 3–6 representing a poor prognosis. Multivariate models were established to investigate severity correlation and prognosis association. Results Serum IRAK3 levels were significantly elevated at the admission of patients, peaked at day 1, plateaued at day 3, gradually declined until day 15, and were substantially higher over the first 15 days poststroke than in controls. Admission serum IRAK3 levels were independently associated with NIHSS scores, hematoma volume, and 6-month mRS scores in a multivariate linear regression model. They were linearly correlated with the risk of poor prognosis in a restricted cubic spline analysis and were independently predictive of poor prognosis in a binary logistic regression model. Additionally, they demonstrated strong prognostic ability in the receiver operating characteristic curve analysis. Using subgroup analysis, no interactions were found between admission serum IRAK3 levels and some routine variables, such as age, gender, hypertension, and diabetes mellitus. Moreover, the model combining admission serum IRAK3, NIHSS scores, and hematoma volume demonstrated stability and clinical value in calibration and decision curve analyses. Conclusion A significant increase in serum IRAK3 levels during the early phase after ICH, strongly correlated with disease severity, is independently associated with a poor 6-month prognosis, establishing serum IRAK3 as a valuable prognostic biomarker for ICH.